Analysis of Student Perceptions on the Use of Interactive Mathematics Learning Media - Dewi, Utami; Atik Prihatini; Surya Amami Pramuditya; Neneng Aminah (PT Inovasi Pratama Internasional, 2024)
This study analyzes students' perceptions of using Quizizz as an interactive mathematics learning media in the classroom. Quizizz media was chosen because Quizizz is the most popular among teachers and students. Using a quantitative descriptive method, the study involved 60 grade X high school students who had used Quizizz. Data were collected through a Likert-scale-based closed questionnaire, measuring ease of use, learning benefits, and student engagement. The analysis showed that students had positive perceptions of Quizizz, with 80% stating that the platform was easy to use, 75% feeling that Quizizz helped them understand the material, and 70% feeling more motivated. Linear regression tests showed a significant relationship between ease of use, learning benefits, and student engagement in learning motivation. Most students felt more active and motivated while using Quizizz, most likely due to the competitive elements such as the leaderboard and point system. These elements not only boost students' intrinsic motivation but also generate extrinsic motivation through healthy competition among students. The more positive students' perceptions of Quizizz, especially in ease of use and learning benefits, the higher their motivation to participate in the learning process. This study concluded that Quizizz is an effective mathematics learning media, improves learning outcomes, and motivates students to be more actively involved in learning.